WEB-BASED CHURCH WORSHIP SERVICE INFORMATION SYSTEM USING THE SPIRAL MODEL: A CASE STUDY OF GKPI AIR BERSIH - Wijaya Sipahutar; Fahrul Rozi Lubis (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The church as a religious institution requires effective management to support worship activities, congregation administration, and financial accountability in complex organizational and technological environments today. At GKPI Air Bersih Church, manual recording practices cause data inaccuracies, reporting delays, limited information access, and difficulties in monitoring congregation finances across sectors effectively. This study aims to design and implement a web-based church worship service management information system using the Spiral development model for integrated digital administration. The research employs a system development methodology involving requirement analysis, iterative design, implementation, evaluation, and continuous user feedback throughout multiple development cycles within the church environment. Data were collected through observation, interviews, and document analysis to identify operational needs, workflow limitations, and technical risks within the church context during system planning. The developed system integrates congregation management, worship scheduling, church bulletins, financial transactions, reporting, user management, and website configuration modules into a single centralized web platform. System evaluation using user acceptance testing indicates improved administrative efficiency, higher data accuracy, and increased transparency compared to manual processes previously used by church administrators. Real-time dashboards, automated calculations, and reporting features support informed decision-making, strengthen accountability, and enhance service quality for administrators and congregation stakeholders effectively overall. The application of the Spiral model enables adaptive development, risk mitigation, usability improvement, and alignment between system functionality and user requirements through iterative evaluation cycles. This research demonstrates the effectiveness of web-based information systems in supporting digital transformation within religious institutions and community organizations with limited technical resources available.